A Comparison of Respiratory Functions, Functional Capacity and Quality of Sleep in Patients with OSAS and COPD Compared to Healthy Controls - Ebru Çalık Kütükcü; Hakan Çalışkan; Kübra Kılıç; Naciye Vardar Yağlı; Nurel Ertürk; Melda Sağlam; Deniz İnal İnce; Hikmet Fırat; Sadık Ardıç; Melike Yüce Ege; Lütfi Çöplü; Sema Savcı; et al. (Türk Uyku Tıbbı Dergisi, 2020)

(untitled)
Objective:The purpose of this study was to compare the respiratory functions, exercise performance, and quality of sleep in patients with Obstructive Sleep Apnea syndrome (OSAS) and Chronic Obstructive Pulmonary disease (COPD) compared to healthy individuals.Materials and Methods:Seventeen patients with OSAS (12 M, 5 F), 24 patients with COPD (20 M, 4 F) and 20 healthy subjects (15 M, 5 F) participated in this cross-sectional study. Respiratory function and muscle strength tests were performed. Knee extensors, shoulder abductors, and hand grip strength were measured in patients with OSAS and COPD using a digital hand-held dynamometer. Exercise performance was evaluated using a 6-minute walk test (6MWT), and sleep quality was assessed by the Pittsburgh Sleep Quality index (PSQI).Results:The 6MWT distance, 6MWT% distance, actual and percentage values of shoulder abductors muscle strength of patients with COPD were significantly lower than those of the OSAS group (p<0.05). According to PSQI recordings, 58.8% of OSAS patients’ sleep quality, 58.3% COPD patients’ sleep quality, and 15.0% of healthy individuals’ sleep quality were poor (p=0.006). The PSQI-sleep disturbance, daytime dysfunction, habitual sleep efficiency subdimensions, and total scores of PSQI in OSAS and COPD group were higher than those of healthy individuals (p<0.05).Conclusion:This study showed that sleep quality is adversely affected in both OSAS and COPD patients and sleep disturbance and daytime dysfunction increases and habitual sleep efficiency decreases in OSAS and COPD patients compared to those of healthy individuals.